SYNTHESIS AND BIOLOGICAL ACTIVITY OF 2-(THIAZOLIDIN-4-ONE) PHENYL]-1H-PHENYLBENZIMIDAZOLES AND 2-[4-(AZETIDIN-2-ONE)-3-CHLORO-4- PHENYL] -1H-PHENYL BENZIMIDAZOLES (International Journal of Pharmaceutical Sciences and Drug Research, 2010)
A new series of 2-[4-(azetidin-2-one)-3-Chloro-4-phenyl]-1H-Phenylbenzimidazoles and 2-(thiazolidin-4-one)-Phenyl]-1H-Phenylbenzimidazoles were synthesized by the reaction of schiff base [2-(4-aminophenyl)-Benzimidazole and substituted Benzaldehyde] with chloroacetyl chloride and mercaptoacetic acid respectively. The chemical structures of the synthesized compounds were confirmed by IR, 1H-NMR, mass spectral and C, H, N analysis. The synthesized compounds were screened for antibacterial (Bacillus cereus, Escherichia coli, Micrococcus luteus, Klebssiela pneumoniae, Staphylococcus aureus and Salmonella epidermidis), antifungal (Aspergillus niger and Candida albicans), analgesic activity by writhing reflex method and anti-inflammatory activity by carrageenan induced paw edema method. The synthesized compound showed significant activity of antibacterial, antifungal, analgesic and anti-inflammatory activity comparable to that of standard.